PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA PADA MATA PELAJARAN IPA - Putri, Melisa; Sucilestari, Ramdhani; Hamzan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a Problem Based Learning (PBL) based Student Worksheet (Lembar Kerja Peserta Didik/LKPD) to improve students’ science process skills in science subjects for fifth-grade students at SDN 43 Cakranegara. The Merdeka Curriculum requires innovative teaching materials that are relevant to students’ needs in order to develop 21st-century skills, particularly science process skills in science learning. However, the teaching materials used at SDN 43 Cakranegara were still limited and had not actively involved students in the learning process, resulting in science process skills that had not developed optimally. Therefore, this study aimed to produce a valid, practical, and effective PBL-based LKPD for science learning.This research employed a Research and Development (R&D) method using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The research subjects included material experts, language experts, media experts, teachers, and fifth-grade students at SDN 43 Cakranegara. Data were collected through validation questionnaires, response questionnaires (practicality), and science process skills tests (pre-test and post-test). The validation results from the language expert (80%), material expert (87.5%), and media expert (54%) indicated that the LKPD was categorized as highly feasible. The practicality level based on teacher responses reached 85%, while student responses reached 92.04%, both categorized as highly practical. The effectiveness of the LKPD was demonstrated by an increase in the average score from 33.96 (pre-test) to 69.08 (post-test), with an average N-Gain score of 0.55 in the moderate category. Furthermore, the normality test using Shapiro–Wilk showed a significance value greater than 0.05, indicating that the data were normally distributed. Therefore, hypothesis testing was conducted using the Paired Sample t-test. The results of the paired sample t-test showed a significance value of 0.000 < 0.05, indicating that there was a significant improvement in students’ science process skills after using the using PBL-based student worksheets (LKPD).